2004
DOI: 10.1074/jbc.m406370200
|View full text |Cite
|
Sign up to set email alerts
|

The Traf2- and Nck-interacting Kinase as a Putative Effector of Rap2 to Regulate Actin Cytoskeleton

Abstract: Rap2 belongs to the Ras family of small GTP-binding proteins, but its specific roles in cell signaling remain unknown. In the present study, we have affinity-purified from rat brain a Rap2-interacting protein of ϳ155 kDa, p155. By liquid chromatography tandem mass spectrometry, we have identified p155 as Traf2-and Nck-interacting kinase (TNIK). TNIK possesses an N-terminal kinase domain homologous to STE20, the Saccharomyces cerevisiae mitogen-activated protein kinase kinase kinase kinase, and a C-terminal reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
149
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(154 citation statements)
references
References 48 publications
(77 reference statements)
4
149
0
1
Order By: Relevance
“…It has been shown that RAP2 regulates the actin cytoskeleton via two effectors, PARG1 and TNIK (36,37). In HEK293 cells, TNIK induces actin fiber disassembly and perturbs cell spreading, a function that is promoted by RAP2A (37). A similar regulatory role for RAP2A in cancer cell migration, dependent on actin cytoskeleton remodeling, is likely and is suggested by the current work, which demonstrates in vitro that RAP2A knockdown promotes both migration and invasion of glioma cells.…”
Section: Figure 10supporting
confidence: 56%
See 1 more Smart Citation
“…It has been shown that RAP2 regulates the actin cytoskeleton via two effectors, PARG1 and TNIK (36,37). In HEK293 cells, TNIK induces actin fiber disassembly and perturbs cell spreading, a function that is promoted by RAP2A (37). A similar regulatory role for RAP2A in cancer cell migration, dependent on actin cytoskeleton remodeling, is likely and is suggested by the current work, which demonstrates in vitro that RAP2A knockdown promotes both migration and invasion of glioma cells.…”
Section: Figure 10supporting
confidence: 56%
“…RAP2A is involved in the regulation of dendrite and axonal branches and restrains dendritic outgrowth of neurons (34,35). It has been shown that RAP2 regulates the actin cytoskeleton via two effectors, PARG1 and TNIK (36,37). In HEK293 cells, TNIK induces actin fiber disassembly and perturbs cell spreading, a function that is promoted by RAP2A (37).…”
Section: Figure 10mentioning
confidence: 99%
“…Active Rap1 has also been shown to influence the subcellular localization of Rac and Rho regulatory proteins, leading to localized cell spreading and the formation of cell protrusions (Arthur et al, 2004;Yamada et al, 2005), consistent with positive effects of Rap1 on growth cone and dendritic spine size. On the other hand, Rap2 but not Rap1 interacts with TNIK (Traf2-and Nck-interacting kinase), a kinase expressed in the brain Taira et al, 2004;Zhu et al, 2005). Binding of activated Rap2 enhances the ability of TNIK to decrease F-actin levels and inhibit cell spreading.…”
Section: Discussionmentioning
confidence: 99%
“…RPIP9 expression is activated during malignant breast epithelial transformation and increases with the progression toward an invasive phenotype (15). Tumor necrosis factor receptor-associated factor 2 (Traf2)-and Nck-interacting kinase (TNIK) is a recently identified Rap2-specific effector that is distinct from RPIP8 (16,17). TNIK interacts with Rap2 through its C-terminal regulatory domain, termed the CNH domain, and regulates the actin cytoskeleton.…”
mentioning
confidence: 99%